Odnosi z vlagatelji - Razpet, Aleš (Teorija in praksa, 1998)
This item is discussed as a specific "branch" of public relations. Regarding other stakeholders, investors have some interesting specifications which affect the management of the relations between investors and an organisation. Invetors found organisations and provide financial means to enable their operations, growth and development. Investor relations help building the competitiveness of organisation on capital markets and preventing unwanted surprises in the ownership structure. Due to the specifications of transitional period, Slovenian privatisation model and poorly developed capital market, the managing of investor relations in Slovenian circumstances is essentially different from one in highly developed market economies.
Keywords: odnosi z javnostmi; investicije; financiranje; pravne osebe